Europeanism and Nationalist Populism: The Europeanization of Greek Civil Society and Foreign Policy - Kalpadakis, George; Sotiropoulos, Dimitri A. (Études helléniques / Hellenic Studies, 2007)
The foreign policy discourse adopted by civil society actors in Greece may be described in terms of an ideological contrast between “Europeanism” and “nationalist populism”. This discourse has pervaded Greek politics, particularly foreign policy, at least since the early 1980s. By examining the consequences of certain events for Greek politics, e.g. the domestic political crisis of 1989, the wars in Yugoslavia, as well as the Europeanization of Greece, we interpret the ways in which civil society has assumed a significant role in Greek foreign policy. In 1989-1996, civil society actors imbued by the nationalist populist discourse prevailed over pro-European, anti-nationalist voices. After 1996, the drive towards European integration and the growing bipartite (PASOK - New Democracy) convergence in foreign policy stimulated the rise of pro-European civil society actors.